Human needs in COVID-19 isolation - Matias, T.; Dominski, F. H.; Marks, D. F. (Journal of Health Psychology, 2020)
To reduce the spread of COVID-19, the World Health Organization and the majority of governments have recommended that the entire human population should `stay-at-home`. A significant proportion of the population live alone or are vulnerable to mental health problems yet, in the vast majority of cases, individuals in social isolation have no access to mental healthcare. The only resource is people themselves using self-help, self-medication and self-care. During prolonged COVID-19 isolation, an in-built system of homeostasis can help rebalance activity, thought and feeling. Increased physical activity enables a reset of physical and mental well-being. During periods of lockdown, it is recommended that exercise should be as vigorously promoted as social distancing itself.